Short-term capital flows, exchange rate expectation and currency internationalization: Evidence from China - Mingming Li; Fengming Qin; Zhaoyong Zhang (Journal of Risk and Financial Management, 2021)
This paper intended to employ a portfolio approach to assess the effect of exchange rate expectation on Chinese RMB internationalization and empirically test the interactive effects among short-term capital flows, RMB appreciation expectation and the internationalization process using a VAR model with monthly data ranging from February 2004 to December 2020. The results suggest that RMB exchange rate appreciation could lead to an increase in the foreign demand for RMB and RMB denominated assets, while RMB internationalization would attract more short-term capital inflow due to the reduced transaction costs. The empirical evidence from the VAR model estimation confirms the finding that expected RMB appreciation induces short-term capital inflow and promotes RMB internationalization. The robustness checks confirm the evidence. The results have important policy implication for RMB internationalization and for maintaining a sound and stable financial system.
Keywords: 330; interactive mechanism; RMB exchange rate expectation; RMB internationalization; short-term capital flow